Bounding-Volume Hierarchies Technique for Detecting Object Interference in Urban Environment Simulation - Sulaiman, H.A.; Bade, A.; Suaib, N.M. (2009 Second International Conference on Environmental and Computer Science, 2009)
Performing and detecting object interference or collision detection in urban environment simulation is always challenging problem for researchers to come out with fast and efficient collision detection algorithm. Most of previous method seems trying to tackle the problems of involving specific geometric models colliding pairs with restricted rules and guidelines. For example, convex hull bounding-volume tends to solve the collision detection problems by make the collision more accurate. However, its limitation of performing fast collision detection method must be left behind. Hence, in this paper we introduce new traversal algorithm using bounding-volume hierarchies (BVH) for collision detection in urban environment simulation. By using hierarchical approach, the efficiency of detecting object interference in urban simulation is increase. We believe that BVH method can be useful in urban simulation for collision detection between static rigid models and dynamic rigid models. Thus it should be able to overcome the equipment of urban environment simulation. Our result shows that bounding-volume hierarchies achieve favorable frame-rates in real time simulation using top-down binary tree. In practice, the construction of bounding-volume hierarchies in urban environment simulation are not just useful for collision detection but they also useful for others detecting object interference technique such culling and raytracing.